Transmaterial Worlding. Beyond Human Systems - Simon, Gail; Salter, Leah K (Murmurations: Journal of Transformative Systemic Practice, 2019)
In this paper we reframe systemic social construction as transmaterial worlding to include human and non-human participants. We discuss what it means to be human in the Anthropocene era with reference to posthuman new materialist theory. We introduce systemic living as onto-epistemological becoming, movement and meaning-making practices in and between human and non-human parts of our worlds. The paper discusses power relations and ways of bringing forth lost-destroyed indigenous ways of knowing which make time and space for new understandings and experimental responses to what we are making together at a local and global level. We discuss how transmaterial worlding requires a new understanding by humans to see their place in this planet as co-inhabitation. We offer examples of transmaterial worlding from across different contexts and suggest some systemic questions for how we can live ethically in a transmaterial world that honours societal, cultural, professional and other kinds of situated knowledge and know-how.